Fundamentals of automatic process control - Chaudhuri, Uttam Ray; Chaudhuri, Utpal Ray (Chemical industries, 2013)
"Modern plants require operators and engineers to have thorough knowledge of instrumentation hardware as well as good operating skills. Chemical engineers need to know about the appropriate use of both control hardware and software and must be able to select/write computer programs that interface the hardware and software to run a plant effectively. This book provides an integrated introduction to the hardware and software of automatic control systems. It solves problems from the GATE examination and provides explanations for each solution. It also includes various examples of control systems commonly used in plants, Laplacian mathematics with solutions, as well as virtual laboratory software"--Provided by publisher.